THE SPECIFICS OF FUNCTIONING OF FINTECH COMPANIES IN UKRAINE DURING WARTIME AND POST-WAR PERIODS (Development Service Industry Management, 2024)
The article explores the peculiarities of FinTech companies' operation in Ukraine during both wartime and post-war periods. It conducts an analysis of the impact of military conflict on the FinTech sector and identifies challenges and opportunities arising in these conditions. The study examines the essence of financial innovations and their role in stimulating economic development during instability. Additionally, it investigates international and Ukrainian experiences in the FinTech sphere and highlights strategies that can contribute to the effective functioning of FinTech companies in wartime and post-war times. The research findings can be beneficial for policymakers, financial institution managers, and all stakeholders interested in the development of the financial sector in unstable conditions. The study emphasizes the importance of adapting FinTech companies to changing conditions and developing reserves to maintain stability and competitiveness during conflict. Furthermore, it explores opportunities for collaboration between FinTech companies and governmental bodies to ensure effective regulation and create a favorable environment for sector development. The conclusions of this article aim to deepen understanding of the relationship between FinTech innovations and conflict conditions, as well as to identify opportunities for enhancing the resilience and efficiency of the FinTech sector in Ukraine amidst instability.
Keywords: digital; FinTech companies; artificial intelligence; digitization; enterprises; development